The price analysis of dressed chicken in Zamboanga City from 1990-1995 - Morales, Precious Hope L; Sunaz, Joselito (1998.)
This research project was conducted to describe the trend of monthly price per kilo of dressed chicken meat in Zamboanga City from 1990-1995 and to identify and analyze the different components which are known as the trend, seasonal, cyclical and irregular that affects the price of chicken meat and this can be obtained by using the Multiplicative Time Series Model. The result of this could be a great help to the consumers and to the government policy-makers to make necessary regulations pertaining to the prices per kilo of dressed chicken. There were only two similar studies on time series have been found and they're concerned with the prices of prawn in the Philippines from 1980-1986 by Villanueva and retail prices of regular and well-milled rice in Iloilo from 1985-1989 by Jusayan., Results of the study show that there was an increasing trend in the monthly price per kilo of dressed chicken in Zamboanga City from 1990 to 1994. The said intensified broiler production made an even greater supply of chicken and made fresh dressed chicken meat more readily available to Zamboanga consumers. Since this is a pioneering research, further related studies should be done.
Research Project (Undergraduate, Bachelor of Arts in Economics-Management) College of Arts and Sciences, UP Visayas, Miagao, Iloilo
Keywords: Dressed Chicken -- Zamboanga City -- 1990-1995.